2012
DOI: 10.1029/2012ja017845
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and diurnal variation of geomagnetic activity: Russell‐McPherron effect during different IMF polarity and/or extreme solar wind conditions

Abstract: [1] The Russell-McPherron (R-M) effect is one of the most prevailing hypotheses accounting for semiannual variation of geomagnetic activity. To validate the R-M effect and investigate the difference of geomagnetic activity variation under different interplanetary magnetic field (IMF) polarity and during extreme solar wind conditions (interplanetary shock), we have analyzed 42 years interplanetary magnetic field and geomagnetic indices data and 1270 SSC (storm sudden commencement) events from the year 1968 to 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
60
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 40 publications
(49 reference statements)
4
60
2
Order By: Relevance
“…The < Dst > values are all negative and reveal unambiguously the R‐M effect with larger disturbances near the March/September equinoxes when the prior IMF B Y (GSE) has been predominantly negative/positive, respectively. As noted by Zhao and Zong [], this is a unique signature of the R‐M effect. The number of storm hours with Dst o < Dst o (for which values are always positive) does show this effect, but it is much less pronounced.…”
Section: Analysis Of Near‐earth Interplanetary Data From 1996–2015mentioning
confidence: 65%
See 1 more Smart Citation
“…The < Dst > values are all negative and reveal unambiguously the R‐M effect with larger disturbances near the March/September equinoxes when the prior IMF B Y (GSE) has been predominantly negative/positive, respectively. As noted by Zhao and Zong [], this is a unique signature of the R‐M effect. The number of storm hours with Dst o < Dst o (for which values are always positive) does show this effect, but it is much less pronounced.…”
Section: Analysis Of Near‐earth Interplanetary Data From 1996–2015mentioning
confidence: 65%
“…Russell and McPherron [] argued that the R‐M effect was the cause of the enhanced occurrence of large geomagnetic storms at the equinoxes. A key test of the idea that the R‐M effect is central to any semiannual variation was made by Zhao and Zong []. These authors showed that which of the two equinoxes was favored in generating geomagnetic activity depended on the polarity of the IMF B Y (GSE) component.…”
Section: Analysis Of Near‐earth Interplanetary Data From 1996–2015mentioning
confidence: 99%
“…The daytime and nighttime SAO relation to geomagnetic activity and particle fluxes could be explained by the semiannual variation in geomagnetic activity (Svalgaard, ). Using Figure of Zhao and Zong (), and according to the method we use to differentiate between daytime and nighttime variability, we can apply the Russell‐McPherron effect (Russell & McPherron, ) and the equinoctial hypothesis, respectively, to explain the SAO observed in the VLF amplitude variations. The main difference between these two semiannual variations is that the equinoctial hypothesis is related to modulation of the existing geomagnetic activity, while the Russell‐McPherron effect is producing the geomagnetic activity (Svalgaard, ).…”
Section: Discussionmentioning
confidence: 99%
“…This effect is called “Russel‐McPherron effect” (R‐M effect). This effect is a coupling effect between Geocentric Solar Magnetospheric (GSM) coordinate system and Geocentric Solar Equatorial (GSE) coordinate system causing the average IMF oriented at the Parker spiral angle project a southward component at Earth (Zhao & Zong, ). Therefore, at the Spring equinox the negative B y in GSE coordinates can provide a maximum southward Bz in the GSM coordinates, and at the Autumn equinox the positive B y in GSE coordinates can provide a maximum southward Bz in the GSM coordinates.…”
Section: Introductionmentioning
confidence: 99%